Nilai - Nilai Pendidikan AKhlak Pada Kitab Tanbih Al - Ghafilin Karya As - Samarqandi Dan Implikasinya Dalam Pencegahan Bullying - Ramadhan, Muhammad Roshan; Matsum, Hasan; Nasution, Zulkipli (PT. Kreasi Karya Majakata, 2024)
The purpose of this research is to find out the Moral Education Materials in the Book of Tanbih Al - Ghafilin by Shaykh Abu Laits As-Samarqandi which can give rise to Moral Education Values that are useful for bullying prevention. This study uses a qualitative research method (library research) with the content analysis method, the researcher collects data with data collection techniques through reading literature that supports research and documentation. The results of this study show that there are moral education values that can prevent bullying in moral education materials in the Book of Tanbih Al - Ghafilin by Shaykh Abu Laits As-Samarqandi according to its nature, namely about moral mahmudah, namely: Morality towards Allah SWT, namely repentance, khauf, sincerity, tawakkal and tafakkur. Morals towards oneself are heroism, gratitude, haya', patience, prohibition of laughing out loud, prohibition of lying, restraint of emotions, maintenance of speech, virtue of gaining knowledge. Morals towards the family are friendship and amar ma'ruf nahi munkar. Morals towards the community are soft-hearted (generous), mercy and compassion, charity with knowledge. And about the morals of madzmumah include: arrogant, ujub, ghibah, namimah, hasad, tyranny, greedy and delusional